Housing for the elderly and digital technologies. Perspectives, processes and future scenarios - Mangiatordi, Anna (AGATHÓN | International Journal of Architecture, Art and Design, 2020)
In the context of an Ageing Society, the technological innovation produced by Digital Age discovers new frontiers and research areas on the topic of living and urban spaces for the elderly. The opportunities offered by the integration of ICTs in the built environment prefigure new settlement scenarios based on the introduction of innovative digital services. Starting from the study of ‘smart homes’ prototype models, the contribution proposes a critical reflection on processes, products and services that could be implemented in future housing for the elderly, facilitating new forms of well-being, security and social inclusion. Compared to ongoing experimental researches, new possible dynamics of innovation in processes and products are delineated, hypothesizing the application of smart systems to real living environments for the elderly.